Topology influence on TCP congestion control performance in multi-hop ad hoc wireless - N., Haniza; M.N., Md Khambari; S., Shahrin; Habbal, Adib M. Monzer; Hassan, Suhaidi (World Academy of Science, Engineering and Technology, 2012)
Wireless ad hoc nodes are freely and dynamically self-organize in communicating with others.Each node can act as host or router.However it actually depends on the capability of nodes in terms of its current power level, signal strength, number of hops, routing protocol, interference and others.In this research, a study was conducted to observe the effect of hops count over different network topologies that contribute to TCP Congestion Control performance degradation.To achieve this objective, a simulation using NS-2 with different topologies have been evaluated.The comparative analysis has been discussed based on standard observation metrics: throughput, delay and packet loss ratio.As a result, there is a relationship between types of topology and hops counts towards the performance of ad hoc network.In future, the extension study will be carried out to investigate the effect of different error rate and background traffic over same topologies.